2013
DOI: 10.15835/nsb549124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Orientation and Medium Strength on <i>In vitro</i> Germination of <i>Pterocarpus marsupium</i> Roxb.

Abstract: A method was developed for optimization of In vitro germination of an economically important timber-yielding multipurpose tree, Pterocarpus marsupium Roxb. The seeds inoculated in different orientation on different strengths of MS medium without any hormones showed varied response to the seed positions. The seeds inoculated on half strength medium in horizontal position recorded to produce a maximum germination (78.23%), shoot number (0.86) and root number (7.99). However, a maximum of shoot length of 3.67 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…These results may be ascribed to the osmotic pressure of the fullstrength MS medium. In accordance with current results, Mishra et al [2013] reported that seed germination of Pterocarpus marsupium inoculated on half strength MS medium in horizontal orientation was significantly higher than on media of other strengths. The results of incubation conditions for in vitro cultures indicated that neither the seeds cultured on the full-strength MS medium nor those cultured on halfstrength one germinated during the first two weeks when incubated at 25 ±1°C with 16 hours light and 8 hours dark.…”
Section: Discussionsupporting
confidence: 92%
“…These results may be ascribed to the osmotic pressure of the fullstrength MS medium. In accordance with current results, Mishra et al [2013] reported that seed germination of Pterocarpus marsupium inoculated on half strength MS medium in horizontal orientation was significantly higher than on media of other strengths. The results of incubation conditions for in vitro cultures indicated that neither the seeds cultured on the full-strength MS medium nor those cultured on halfstrength one germinated during the first two weeks when incubated at 25 ±1°C with 16 hours light and 8 hours dark.…”
Section: Discussionsupporting
confidence: 92%
“…The best growth in shoot length of Byrsonima cydoniifolia cultivated on different media was obtained on water-agar medium (Solanki, Siwach 2012). Seed culture of Givotia rottleriformis (Rambabu et al 2006) and Pterocarpus marsupium (Chathurani et al 2009;Mishra et al 2013) showed decrease in shoot length of seedlings germinated on full MS compared to half strength. Chathurani et al (2009) suggest that the levels of salts in MS medium may have been unnecessarily high, resulting in slowing growth or even toxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…[12]. Different basal media [10], salts strength [13], type and concentration of plant growth regulators [14], and mature and immature seed [15] have been used for germination and propagation.…”
Section: Introductionmentioning
confidence: 99%